SecureOps: Toward Resilience for Security and Privacy in Industrial Applications - Silva, Hebert; Santos, Rodrigo; Guerino, Oliver (Anais do Workshop sobre Engenharia de Resiliência em Sistemas de Computação (RECS); 2024: Anais do I Workshop sobre Engenharia de Resiliência em Sistemas de ComputaçãoDO - 10.5753/recs.2024.35962, 2024)
The SecureOps Lab was established to tackle cybersecurity challenges in Cyber-Physical Systems (CPS), Operational Technology (OT), and the Internet of Things (IoT). Despite the opportunities these technologies offer, their complexity makes them vulnerable to cyber attacks. The lab combines physical and virtual environments to develop, validate, and verify resilient security solutions, simulating real-world scenarios to ensure practical and robust outcomes using the Technology Readiness Level (TRL) framework. As a controlled environment, the lab explores vulnerabilities, tests defense mechanisms, and enhances resilience in security solutions. This work presents initial results and discusses a case study involving a Proof of Concept (PoC) of the Purdue Model using Fortinet’s IoT Solution.